Estimation of parameters for faulted transposed transmission lines - Pineda, Julia Teresa Rivera [UNESP] (2018)
This paper presents a method to estimate transmission line parameters for transposed lines from faulted current and voltage measurements at the line's terminals, in the time domain. The measurements are transformed to the modal domain, using Clarke's transformation matrix, and related to the modal impedance and admittance using theπ-circuit representation. The lumped modal parameters calculated by the least square method are firstly distributed along the line and finally converted to the phase domain. The method is tested for both short and open circuit faults and proved invariant and precise for transmission lines within 800km of length.